ESG and firm performance: Evidence from the Nordic countries - Vaihekoski Mika; Yahya Habeeb (Association of Business Schools Finland, 2025)
This study examines the relationship between ESG and firm financial performance and market valuation using data on publicly listed firms in the Nordic countries from 2010 to 2020. The results show that ESG scores and individual pillar scores are positively related to profitability and firm valuation except for the governance pillar score which is negatively related to profitability. Further analysis shows a bi-directional relationship between ESG and firm profitability. This aligns with earlier studies suggesting that corporate sustainability is a predictor as well as a consequence of corporate financial performance.